Analisis Kariometric Akibat Pemberian Variasi Dosis Aspartam pada Perkembangan Fetus Mencit (Mus Musculus L.) - Esti Novi Andyarini; Nova Lusiana; Ika Mustika; Estri Kusumawati; Sri Hidayati; Moch Irfan Hadi; Risa Purnamasari; Dedy Suprayogi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Aspartame is safe for consumption according to the prescribed ADI, but this artificial sweetener is not nutritious or does not contain calories so it is not recommended to be consumed during pregnancy. This study was to analyze cariometric effect of aspartame doses in the development of fetal mice (Mus muculus L.). The type of research used was experimental laboratory research on 24 adult mice with 4 treatment groups, control, aspartame dose 13 mg / Kg BB, 39 mg / Kg BB and 78 mg / Kg BB. Data was analyzed using SPSS 16 with one way ANOVA. Based on the results of the study there were changes in the number and weight of the fetus due to aspartame doses, there was no change in fetal length due of aspartame dose variations. Consumption of aspartame during pregnancy should be avoided because it can cause teratogenic effects. For further research, it is necessary to observe the morphology and histology of the fetus which is expressed by aspartame to determine the types of congenital abnormalities.